Share The Music : Introduction To Computers In Music - Ray Dretske; Alison Ellwood; Amy J Kaufman (McGraw-Hill School Publishing Company, 1997)
Music technology is the perfect tool for nurturing creativity in young people. In this video, educator Ray Dretske demonstrates how computer technology changes and enhances the way we create and perform music. He combines computer-generated sounds with those of acoustic instruments to illustrate the musical possibilities computer technology offers.